ANALISIS SEBARAN TUTUPAN VEGETASI MENGGUNAKAN CITRA LANDSAT 8 DI KECAMATAN ULUJADI KOTA PALU - Hangu, Nurhadi S. Laode; Akhbar, .; Arianingsih, Ida (Universitas Tadulako, 2018)
Ulujadi is one of sub-district in Palu city which continues opening new lands for residential areas as well as sand and stone quarry, consequently the distribution of existing vegetation to be reduced. Along with the continued occurrence, conversion of existing land in urban areas particularly in Ulujadi Sub-District. Therefore, it is necessary to do extensive research to analyze the extent of vegetation cover distribution. Distribution of vegetation analysis was carried out using a descriptive method of photogrammetry approachment was image interpretation that executed digitally to obtain data and information of vegetation cover distribution by utilizing Landsat 8 image directly on the computer monitor of software ArcGIS 10,2 supervised classification. Vegetation index is counted NDVI (Normalized Difference Vegetation Index) by utilizing band 5 (Infrared) and band 4 (Red) of Landsat 8. The result of analysis of vegetation distribution used Landsat 8 image of 2016 path/row 115/61 at Ulujadi Sub-District of Palu City, obtained land which vegetated of width 5222,47 Ha or 82,04 % and unvegetated land 1143,28 Ha or 17,96 %. Vegetation distribution at Ulujadi that consists forest land, shrubs and savanna each has extensive are forest (1498,79 Ha or 23,54 %), shrubs ((3704,23 Ha or 58,19 %) and savanna (19,45 Ha or 0,31 %). NDVI value at Ulujadi has a value between -0,13 - 0,6. The NDVI value for sparse canopy density class has large-scale of 358,16 Ha (6,86 %), medium canopy density has large-scale 856,16 Ha (16,39 %), while the dense canopy density has large-scale 4.008,15 Ha (76,75 %).Keywords : Vegetation Distribution, Landsat 8 Image, Ulujadi Sub-District